Narkoterorisme Sebagai Ancaman Bonus Demografi : Perspektif Sekuritisasi Ketahanan Nasional - Fahriani, Ade Aryanti; Akustyo, Bagus Ridho; Agustina, Saur Martha (Jurnal Kajian Stratejik Ketahanan Nasional, 2023)
The proliferation of narcotics issues in Indonesia has grown increasingly complex, impacting social security and national resilience. The substantial profit from the narcotics trade presents opportunities as a financing avenue for acts and terrorist groups. The integration of narcotics trade with illicit activities creates the potential for connection and convergence between drug trafficking criminal organizations and terrorist organizations, as known as narcoterrorism. Despite the forthcoming demographic bonus in Indonesia, the younger generation is overshadowed by radical ideologies, and the abuse and illicit trafficking of narcotics, which could jeopardize the quality of the demographic bonus. Therefore, there is a perceived need to securitize the threat of narcoterrorism, which poses a vulnerability as a threat to the future younger generation. This research aim to analyze the phenomenon of narcoterrorism as a potential threat to the demographic bonus in Indonesia within the framework of national resilience securitization. This study employs qualitative methodology with a literature review approach. The result indicate that government efforts to address terrorism threats and narcotics crimes are disjointed, resulting in suboptimal securitization efforts concerning the narcoterrorism threat. Consequently, there is a necessity for the development of measures related to narcoterrorism, particularly in terms of more specific regulations and policies.